In-situ and Real-Time Monitoring of the Interaction Between Lysins and Staphylococcus aureus Biofilm by Surface Plasmon Resonance - Hong, Wei; Nyaruaba, Raphael; Li, Xiaohong; Liu, Huan; Yang, Hang; Wei, Hongping (Frontiers in Microbiology, 2021)
Staphylococcus aureus can produce a multilayered biofilm embedded in extracellular polymeric matrix. This biofilm is difficult to remove, insensitive to antibiotics, easy to develop drug-resistant strains and causes enormous problems to environments and health. Phage lysin which commonly consists of a catalytic domain (CD) and a cell-wall binding domain (CBD) is a powerful weapon against bacterial biofilm. However, the real-time interaction between lysin and S. aureus biofilm is still not fully understood. In this study, we monitored the interactions of three lysins (ClyF, ClyC, PlySs2) against culture-on-chip S. aureus biofilm, in real-time, based on surface plasmon resonance (SPR). A typical SPR response curve showed that the lysins bound to the biofilm rapidly and the biofilm cracking started at a longer time. By using 1:1 binding model analysis, affinity constants (KDs) for ClyF, ClyC, and PlySs2 were found to be 3.18 ± 0.127 μM, 1.12 ± 0.026 μM and 15.5 ± 0.514 μM, respectively. The fact that ClyF and PlySs2 shared the same CBD but showed different affinity to S. aureus biofilm suggested that, not only CBD, but also CD affects the binding activity of the entire lysin. The SPR platform can be applied to improve our understanding on the complex interactions between lysins and bacterial biofilm including association, disassociation, and biofilm cracking.